Currency union and foreign direct investment inflow: Evidence from Economic Community of West African States (ECOWAS) - Anokye M. Adam (SPOUDAI - Journal of Economics and Business, 2013)
This study investigates the effect of currency union membership on foreign direct investment inflow to ECOWAS subregion. The study employed panel dynamic ordinary least square (DOLS) to estimate a panel data of fifteen ECOWAS countries from 1995 to 2010 with the framework of the gravity model. The result indicates a positive effect of a currency union on FDI inflow to ECOWAS, which shows that the presence of a currency union is likely to increase FDI by 46%. The control variables; political constraint, current account and trade openness is significant in explaining FDI inflow to ECOWAS. The implications of the findings are that currency union positively influences the flow of FDI into ECOWAS region, and this requires stable political environment, financial and trade openness. It goes to suggest that adoption of common currency should go with these factors to maximize the benefit of currency union membership in the region.
Keywords: F15; F21; F30; 330; Currency Union; Foreign Direct Investment; Gravity Model and DOLS